SPAT inhibits LUAD metastasis by targeting SF1-mediated splicing - Yun Ma; Xiaoxu Zhou; Mengqian Yu; Xiang Cheng; Juze Yang; Jiayi Ren; Chengcai Zheng; Jia Li; Xinyi Qian; Jiani Yi; Honghe Zhang; Yan Lu; et al. (Cell Death and Disease)
Abstract Lung adenocarcinoma (LUAD) progression involves alterations in oncogenes and tumor suppressor genes, collectively shaping tumorigenic landscape. However, the precise interactions within this landscape remain inadequately understood. Here, we present a functional characterization of a novel long non-coding RNA (lncRNA), SPAT (splice associated transcript). SPAT is downregulated in LUAD and its expression positively correlates with favorable prognosis. In vitro and in vivo experiments demonstrated that SPAT inhibits the migration of LUAD cells. This inhibitory effect is mediated by SPAT’s interaction with splicing factor 1 (SF1), which disrupts SF1-mediated splicing of KITLG/SCF exon 6, thereby suppressing ERK phosphorylation. Our findings suggest that SPAT acts as a tumor suppressor in LUAD by regulating alternative splicing and highlight its potential as a therapeutic target for managing LUAD metastasis. SPAT suppresses LUAD cell migration by binding to splicing factor 1 (SF1) and disrupting SF1-mediated inclusion of exon 6 in the KITLG/SCF transcript. This shifts KITLG splicing toward increased production of KITLG-201 isoform and reduced KITLG-205, ultimately lowering ERK phosphorylation and limiting metastatic potential.